Penerapan Metode TOPSIS Dan SAW Dalam Menentukan Penerimaan Anggota OSIS Baru - Zufria, Ilka; Suhardi, S; Farentika, Yosi (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2023)
Along with the times, computer technology has increasingly developed its use and is widely used in various fields such as in the fields of health, automotive, economics, education and so on. The rapid development of technology provides many conveniences in solving problems and satisfying work demands for human life. One of the uses of information technology has been implemented in schools. The Intra-School Student Organization (OSIS) is an organization at the school level in Indonesia, starting from junior high school (SMP) and high school (SMA). The Student Council is taken care of and managed by students who are selected to become the Student Council committee. Currently, to accept new student council members, it is only determined by the student council president and several teachers. The assessment process tends to be subjective, so it is not fair. To solve these problems, a decision support system can be applied. with the current development of information technology this research will develop a system that can determine the acceptance of new student council members and apply decision support system techniques using the TOPSIS and SAW algorithms. The research objectives put forward in solving the problem are as follows. Determination of acceptance of OSIS members using the TOPSIS and SAW methods. Designing an application for accepting OSIS members using the TOPSIS and SAW methods using the PHP programming language system and MySQL database.